2015
DOI: 10.4274/tjo.55823
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Dermis-Fat Graft Transplantation: Results in Primary and Secondary Implantation

Abstract: Objectives: Autologous dermis fat graft (DFG) is being used in both primary and secondary socket surgeries. In the present study, we aimed to evaluate patients' satisfaction and possible intra-and postoperative complications in patients who had DFG transplantation. Ma te ri als and Met hods:In this retrospective study, the results of 17 patients who were operated between October 2008 and October 2012 were evaluated. Of these cases, 7 had primary and 10 had secondary DFG. Patient satisfaction was evaluated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We had two patients with complications, one of them, a child, had fornix contraction with fat resorption after DFG, which we believed was due to the history of radiotherapy for retinoblastoma. This effect of radiation, leading to fat resorption and/or fat atrophy was also seen by Karatas et al 15 Our one adult female patient had fornix scarring and conformer extrusion, for unexplainable reason, however the cause of loosing her eye was trauma.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We had two patients with complications, one of them, a child, had fornix contraction with fat resorption after DFG, which we believed was due to the history of radiotherapy for retinoblastoma. This effect of radiation, leading to fat resorption and/or fat atrophy was also seen by Karatas et al 15 Our one adult female patient had fornix scarring and conformer extrusion, for unexplainable reason, however the cause of loosing her eye was trauma.…”
Section: Discussionsupporting
confidence: 81%
“…The final outcome, patient satisfaction and the rate of complications were evaluated. We found out that 10 (83.3%) out of 12 of our DFG patients were satisfied with the aesthetic and functional outcome, whereas Karatas et al 15 evaluated 17 patients out of which 10 patients were operated for secondary DFGs and reported 60% (6 patients) of the patients being satisfied with the results with no major complications, and four patients (40%) were not happy with outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…One study conducted by Huang et al [ 22 ] evaluated the cosmetic results using the 5-point Likert scale (1, very unsatisfied; 2, unsatisfied; 3, neutral; 4, satisfied; 5, very satisfied), and the mean score awarded for patients was 4.702, which was significantly higher than the midpoint value of 3 (average) on the 5-point scale, indicating that patients were mostly satisfied with their overall postoperative improvement. Karataş et al [ 33 ] evaluated patients’ satisfaction by a questionnaire graded from 1 (not satisfied), 2 (mildly satisfied), 3 (moderately satisfied), and 4 (very satisfied). Grades 1 and 2 were accepted as dissatisfaction and grades 3 and 4 were accepted as satisfaction for the data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…18 Postoperative complications such as graft hirsutism, conjunctival cysts, or granulomas are relatively common. 19 DFG is associated with highly variable outcomes, particularly in patients undergoing secondary DFG procedures 20 Previous studies have suggested that the volume augmentation after AFT in the anophthalmic socket can last up to 5 years postoperatively as demonstrated on MRI imaging and photography. 21 However, DFG procedures can offer distinct advantages when both lining and volume augmentation are required.…”
Section: Discussionmentioning
confidence: 99%